Suspected Limbic Encephalitis and Seizure in Cats Associated with Voltage‐Gated Potassium Channel (VGKC) Complex Antibody. (28th December 2012) - Pakozdy, A.; Halasz, P.; Klang, A.; Bauer, J.; Leschnik, M.; Tichy, A.; Thalhammer, J.G.; Lang, B.; Vincent, A.
<x xml:space="preserve">Abstract</x> Background Treatment‐resistant complex partial seizures (CPS) with orofacial involvement recently were reported in cats in association with hippocampal pathology. The features had some similarity to those described in humans with limbic encephalitis and voltage‐gated potassium channel (VGKC) complex antibody. Hypothesis/Objectives The purpose of this pilot study was to evaluate cats with CPS and orofacial involvement for the presence of VGKC‐complex antibody. Animals Client‐owned cats with acute orofacial CPS and control cats were investigated. Methods Prospective study. Serum was collected from 14 cats in the acute stage of the disease and compared with 19 controls. VGKC‐complex antibodies were determined by routine immunoprecipitation and by binding to leucine‐rich glioma inactivated 1 (LGI1) and contactin‐associated protein‐like 2 (CASPR2), the 2 main targets of VGKC‐complex antibodies in humans. Results Five of the 14 affected cats, but none of the 19 controls, had VGKC‐complex antibody concentrations above the cut‐off concentration (>100 pmol/L) based on control samples and similar to those found in humans. Antibodies in 4 cats were directed against LGI1, and none were directed against CASPR2. Follow‐up sera were available for 5 cats in remission and all antibody concentrations were within the reference range. Conclusion and Clinical Importance Our study suggests that an autoimmune limbic encephalitis exists in cats and that VGKC‐complex/LGI1 antibodies may play a role in this disorder, as they are thought to in humans.